The Influence of Pet Attachment with Happiness Levels in Cat Pet Owners in Padang City - Adhilla Inayah Putri; Rizal Kurniawan (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Nowadays, the phenomenon of keeping animals, especially cats, is very common among people. Due to the great interest in cats, communities and groups of cat lovers are formed. In modern times, animals are considered to play a role in fulfilling human needs, one of which is to be happy. One alternative method to increase happiness is to build attachments with animals and obtain social support from them. This study aims to examine the effect of pet attachment on the level of happiness of cat owners in Padang City. This study used quantitative methods with a population of cat pet owners in Padang City and involved a sample of 111 subjects. Data were collected using two scales, namely the happiness scale consisting of 28 items with a reliability coefficient of 0.950, and the pet attachment scale consisting of 21 items with a reliability coefficient of 0.922. Data analysis was carried out using simple linear regression techniques. The results of the study using simple linear regression analysis obtained the results of the correlation value r = 0.331, from the output obtained the coefficient of determination (R Square) of 0.110, the value of F count = 13.417 with a significance level of 0.000 <0.05, it can be concluded that there is an influence between pet attachment and the level of happiness of cat pet owners in Padang City.